Mitotic Cell Division in Caenorhabditis elegans - Pintard, Lionel (Genetics, 2019)
Mitotic cell divisions increase cell number while faithfully distributing the replicated genome at each division. The Caenorhabditis elegans embryo is a powerful model for eukaryotic cell division. Nearly all of the genes that regulate cell division in C. elegans are conserved across metazoan species, including humans. The C. elegans pathways tend to be streamlined, facilitating dissection of the more redundant human pathways. Here, we summarize the virtues of C. elegans as a model system and review our current understanding of centriole duplication, the acquisition of pericentriolar material by centrioles to form centrosomes, the assembly of kinetochores and the mitotic spindle, chromosome segregation, and cytokinesis.